Evaluation of the Competence Strengthening Program of IRE Supervisors Using the Kirkpatrick Model - Amin, Amin; Ulfiah, Ulfiah; Muchtar, Hendi S.; Mudrikah, Achmad (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract.  This research is motivated by a phenomenon in the field showing that Islamic Religious Education (IRE) Supervisors even though they have attended education and training, their competencies are still not optimal, even according to the results of the evaluation of the Directorate of Career Development and Performance Assessment, Ministry of Education and Culture in the last 2 (two) years experiencing decline. This study aims to determine the effectiveness of the implementation of the Education and Training Program for Strengthening the Competence of Islamic Religious Education Supervisors organized by the Bandung Religious Education and Training Center.  Based on the comparison of the success criteria with Kirkpatrick’s evaluation performance, the implementation of the Training Program for Strengthening the Competence of Islamic Religious Education Supervisors was very successful, went as expected and provided useful results, and had contributed to developing the knowledge, attitudes, and skills of supervisors, the program of The Training for Strengthening the Competence of Islamic Religious Education Supervisors can be continued for the next batch.Keywords: Evaluation, Islamic Religious Education (IRE), Kirkpatrick, Education and Training